DESIGN, SYNTHESIS, AND BIO-EVALUATION OF NEW 2-[(5-SUBSTITUTED ARYL-3-MERCAPTO-1H-1, 2,4-TRIAZOL-1-YL) METHYL]-1H-ISOINDOLE-1,3(2H)-DIONE DERIVATIVES - Valarmathy Joshua; L. Samuel Joshua; Sherlyn Joshua; Vinolyn Joshua; W.D. Sam Solomon (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
A new isoindoline-1,3-dione derivatives were synthesized and evaluated for their anti-bacterial activity. The target compounds 2-[(5-substitutedaryl-3-mercapto-1H-1,2,4-triazol-1-yl) methyl]-1H-isoindole-1,3(2H)-dione derivatives were obtained by condensation of N-hydroxymethylphthalimide and thiocarbohydrazide to form 2-[(1,3-dioxo-1,3-dihydro-2H-isoindol-2-yl) methyl] hydrazine-1-carbothioamide and reacted with different aromatic acids. The structures of the synthesized derivatives were confirmed using IR and 1H-NMR spectral data. The antibacterial activity was determined by Mueller–Hinton well diffusion method. The results revealed the importance of the combination of 1,2,4 triazole and phthalimide moieties as a promising antibacterial agent.